The Influence of Marketing Mix on Customer Satisfaction, Trust, and Loyalty - Gloria Ake Christianti; Hartoyo; Nur Hasanah (Jurnal Ilmiah Manajemen Kesatuan, 2025)
In today’s highly competitive food and beverage industry, customer satisfaction, trust, and loyalty have become critical determinants of business sustainability. This study aims to analyze the influence of the 7Ps marketing mix on customer satisfaction and trust, and their subsequent impact on customer loyalty. A quantitative approach was applied by distributing structured questionnaires to 226 respondents aged 18–55 who had purchased within the last three months across selected outlets in Greater Jakarta. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test direct and indirect effects. The results show that product, price, promotion, people, and process significantly enhance customer satisfaction, while only the people dimension significantly builds trust. Furthermore, satisfaction directly strengthens both trust and loyalty, and trust itself exerts a significant impact on loyalty. Indirect effects reveal that product, price, place, promotion, people, and process positively influence loyalty through satisfaction, whereas physical evidence does not. These findings highlight that core elements of the marketing mix, particularly product quality, fair pricing, employee service, and operational efficiency, play a stronger role in fostering long-term customer loyalty compared to physical attributes of the restaurant environment